2018
DOI: 10.1159/000492183
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Demographic and Symbolic Features in Clinical Arabic Graphesthesia Testing

Abstract: Objective: Graphesthesia is the ability to identify a symbol traced on the skin. Agraphesthesia is the impairment in this ability and is encountered in various disorders of the somatosensory pathways. We aimed to describe the demographic and symbolic features that influence correct recognition of Arabic graphesthesia stimuli in healthy Arabic individuals. Methods: Participants were community dwelling healthy Arabian individuals of 18 years of age or older. Demographic information collected included age, gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Alphabetic numbers with unique styles were easier to identify. 24 One more study supports our study results conducted by Daniel S. Harvie and their colleagues concluding that the two-point discrimination illustrated magnificent re-inspection accuracy, comprehensive and confined tests illustrated good results and graphesthesia demonstrated fair reliability. There was no consequential association amid measures.…”
Section: Table I: Demographic Characteristics Of Participantssupporting
confidence: 85%
“…Alphabetic numbers with unique styles were easier to identify. 24 One more study supports our study results conducted by Daniel S. Harvie and their colleagues concluding that the two-point discrimination illustrated magnificent re-inspection accuracy, comprehensive and confined tests illustrated good results and graphesthesia demonstrated fair reliability. There was no consequential association amid measures.…”
Section: Table I: Demographic Characteristics Of Participantssupporting
confidence: 85%
“…Most of studies of Arabic graphesthesia were applied on normal adults; for example, the study that was conducted by Alijafen et al [21] found that female gender, younger age, and higher education are associated with higher scores. On the other hand, there are no enough studies of graphesthesia applied on Arabic-speaking and Arabic-writing children.…”
Section: Discussionmentioning
confidence: 99%